Legal Protection For Consumers Of Parking Services Indonesia In Kabanjahe - Listra Sembiring; Henry Aspan; Hasdiana Juwita Bintang (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Conducting this research aims to find out what the legal relationship is between parking service users and parking service managers and what are the civil responsibilities of parking managers toward consumers of parking services. Using the normative legal research method, it was concluded: in the use of parking, both the manager and the consumer, have a legal relationship, namely the goods safekeeping agreement in this case so that the obligation in the parking agreement is that the consumer surrenders his vehicle to the parking manager to be placed in the parking area he manages, and pays parking fee (service) to the parking manager. The obligation of the parking manager is to maintain and maintain the consumer's vehicle safely while it is parked in the parking service area and must return it to the way it was originally received. Thus the legal responsibility of the parking manager for the loss of goods or vehicles belonging to consumers related to the existence of a standard clause on the transfer of responsibility in parking tickets is that the parking manager is obliged to be responsible for giving compensation to consumers whose vehicles are lost in the parking area managed by the parking manager because the manager parking is proven to have defaulted on the parking agreement which is a goods custody agreement.